Doxycycline Sclerodesis—“Rhinodesis”—for Enhanced Soft Tissue Adhesion in Rhinoplasty: A Preliminary Study - Kovacevic, Milos; Kosins, Aaron M.; Davis, Richard; Al Maamari, Salwa; D'Souza, Alwyn (Facial Plastic Surgery, 2024)
The use of doxycycline as a sclerosing agent is well-established. Given the clinical efficacy of doxycycline sclerosant therapy, we embarked upon a study to evaluate the efficacy of small-volume liquified doxycycline particularly in thick skinned rhinoplasty patients to promote re-adhesion of the nasal skin-soft tissue envelope (SSTE) thereby minimizing surgical dead space and enhancing surface contour, to improve the eventual outcome of surgery.We present two clinical case series using rhinodesis. All patients were treated with the same rhinodesis protocol that included conventional splinting and taping. The first series consisted of 102 consecutive primary rhinoplasties with medium to thick nasal skin treated via open rhinoplasty. Doxycycline solution at a concentration of 20 mg/mL was applied beneath the skin flap using a 14-gauge angiocath inserted through small gaps in the marginal suture line following closure, retained for 2 to 3 minutes, and then expressed from the dead space. Firm manual compression of the SSTE was maintained for at least 1 additional minute, and the splint was then applied. The second series consisted of 25 thick-skinned primary rhinoplasties that were also treated with open rhinoplasty using the same rhinodesis protocol. However, the second group was evaluated with serial postoperative ultrasonography to characterize the soft-tissue response to rhinodesis, particularly within the tip and supra-tip regions.Results revealed enhanced skin adherence in nearly all patients when compared to traditional taping and splinting alone. Ultrasonic examination demonstrated enhanced adherence of the subcutaneous tissue to the nasal framework and suggests that rhinodesis is effective at minimizing dead space in majority of thick-skinned rhinoplasty patients. No complications were observed. Doxycycline can be used easily and safely to seal the surgical dead space post-rhinoplasty and minimize degradation of nasal contour with excellent outcome.
Keywords: doxycycline Sclerodesis; doxycycline; rhinodesis; skin-soft tissue envelope